2016
DOI: 10.1111/jop.12430
|View full text |Cite
|
Sign up to set email alerts
|

THBS1 is induced by TGFB1 in the cancer stroma and promotes invasion of oral squamous cell carcinoma

Abstract: THBS1 is a tumor-specific ECM protein that is induced by TGFB1 and promotes migration of cancer cells and stimulates the expression of MMPs partly through the integrin signaling, thereby favoring OSCC invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 56 publications
(71 reference statements)
2
63
0
Order By: Relevance
“…Other studies have also reported that FAK/Src pathway was associated the OSCC cell migration [32, 33]. Moreover, Pal et al shows that thrombospondin-1 promotes migration of oral cancer cells and stimulates the expression of MMP-11 partly through the integrin signaling [34]. Therefore, we utilized a western blot to characterize the phosphorylation of FAK and Src in the MMP-11-overexpressed TW2.6 OSCC cells and showed that phosphorylation of FAK and Src was significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also reported that FAK/Src pathway was associated the OSCC cell migration [32, 33]. Moreover, Pal et al shows that thrombospondin-1 promotes migration of oral cancer cells and stimulates the expression of MMP-11 partly through the integrin signaling [34]. Therefore, we utilized a western blot to characterize the phosphorylation of FAK and Src in the MMP-11-overexpressed TW2.6 OSCC cells and showed that phosphorylation of FAK and Src was significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…The significant relationship between THBS1 and OC was detected using both RWR-based and SP-based methods. Several studies have indicated that THBS1 has crucial functions in oral tumorigenesis [72, 73]. THBS1 might be a potential diagnostic and therapeutic target for OC.…”
Section: Discussionmentioning
confidence: 99%
“…A paracrine interaction between tumor cells and CAFs lead to up‐regulation of MMP9, which is secreted and activated by OSCC tumor cells . A later study on OSCC found that thrombospondin (THBS) ‐1 released by fibroblasts further stimulated the production of MMP9 and other MMPs, supporting destruction of the ECM and cancer invasion . TGF‐ÎČ enhances MMP9 secretion and also triggers TAFs to secrete IL‐11, which may play a role in tumor progression and metastasis .…”
Section: Fibroblastsmentioning
confidence: 99%
“…Anti-IL-10 antibodies; TLR ligands and agonistic CD40 antibodies, anti-VEGF therapies, intratumoral injection of T. gondii; DC vaccines [24,30] Macrophages Anti-CCL2 antibodies; CSF1 and CSF1R antagonists; TLR ligand CpG and anti-IL-10 antibodies; IkK Kinase b inhibitors; HRG; FRb-targeted therapies; anti-CCL5 therapies; anti-CCL18 therapies; intravesicle installation of M. bovis; agonistic CD40 antibodies Anti-MARCO antibodies [39,44,49,[52][53][54][55][56][57][58][59] Pericytes VEGFR and PDGFR-b antagonists; VEGFR, PDGFR-b, and Tie-2 agonists; anti-RSG5 and anti-PD/PD-L1 therapies [61,68] Endothelial cells avb1, avb2, a5b1 integrin inhibitors; anti-VEGF and VEGFR agents [76,78] Fibroblasts Anti-CXCR-4 antibodies (SDF-1/CXCL12 inhibition); anti-VEGF-A antibodies and VEGF-R inhibitors; anti-PDGF-C/ PDGF-R inhibitors; MMP inhibitors; anti-IL6 antibodies; anti-HGF therapies; anti-FAP antibodies; Anti-TGFb and TGFbR inhibitors; anti-IL-11 therapies; anti-THSB1 therapies [80,86,90,[95][96][97][98] Neuronal cells NT3 and NT4 targeted therapies; GDNF inhibitors; anti-NGF antibodies; anti-PTN antibodies and N-syndecan inhibitors; BDNF inhibitors [99,105,109,111] Adipocytes Anti-IL-6 antibodies; anti-IL-8 antibodies; anti-CCL2 antibodies; anti-TIMP-1 antibodies; COX2 inhibitors, APN [119,120,122] APN, adiponectin; BDNF, brain-derived neurotrophic factor; CCL, chemokine ligand; CD, cluster of differentiation; COX, cyclooxygenase; CSF, colony stimulating factor; CSF1R, colony stimulating factor 1 receptor; CTLA, cytotoxic T-lymphocyteassociated protein; CXCL, C-X-C chemokine ligand; CXCR, C-X-C chemokine receptor; FAP, fibroblast activation protein; FRb, folate receptor beta; GDNF, glial cell line-derived neurotophic factor; HRG, histadine-rich glycoprotein; IL, interleukin; MMP, matrix metalloproteinase; NGF, n...…”
Section: Dendritic Cellsmentioning
confidence: 99%